AN ANALYSIS OF THE GAPS IN THE NEWLY ESTABLISHED SOUTH AFRICAN MILITARY OMBUD - Montesh, Moses; Mmusinyane, Boitumelo (Scientia Militaria - South African Journal of Military Studies, 2013)
The South African Department of Defence and Military Veterans can be commended for having taken a bold step in an endeavour to establish an independent entity capable of conducting oversight of its military through the introduction of the Military Ombud Act. However, said Act seems not to adequately address pertinent issues experienced by the defence sector. These issues include who may submit a complaint, the independence of the Military Ombud (MO) and its accountability structure. Unless the Bill deals with these issues, we are likely to see dispossession of the public protector’s investigation powers and the establishment of a mere toothless tiger. Under the current format of the Bill, the MO is likely to become the Minister’s mouthpiece. It would deepen and marginalise military complainants’ hope of finding a remedy in an independent structure capable of challenging some of the questionable military acts or omissions that have no substance while not achieving the exercise, enjoyment and fulfilment of military complainants’ human rights in accordance with the 1996 Constitution of the Republic of South Africa.